EMODIN EFFICACY ON THE AKT, MAPK, ERK AND DNMT EXPRESSION PATTERN DURING DMBA-INDUCED ORAL CARCINOMA IN GOLDEN SYRIAN HAMSTERS - Manimaran, Asokan; Manoharan, Shanmugam; Neelakandan, Mani (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: The present study has evaluated the Emodin efficacy on the Akt, MAPK, ERK and DNMT expression pattern during 7,12-dimethylbenz[a]anthracene (DMBA)-induced oral carcinoma in golden Syrian hamsters, in order to explore its antitumor potential. Materials and methods: Oral tumors were developed in the buccal pouches of golden Syrian hamsters using the carcinogen, DMBA. Results: While the incidence of tumor formation was 100% in hamsters treated with DMBA alone, the tumor formation was not noticed in DMBA+ Emodin treated hamsters. Also, Emodin reduced the severity of precancerous pathological lesions such as dysplasia, in the hamsters treated with DMBA. Emodin administration corrected the abnormalities in the expression pattern of Akt, MAPK, ERK and DNMT in the buccal mucosa of hamsters treated with DMBA. Conclusions: The present study thus suggests that the tumor preventive potential of Emodin is partly related to its modulating effect on the Akt, MAPK, ERK and DNMT expression pattern, as these molecular markers have a pivotal role in the process of cell proliferation, inflammation, invasion, and apoptosis.